The Search for a Unified Korea Political and Economic Implications - Hwang, Eui-Gak.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
With the leadership of the North Korean political regime in flux, the political and economic relationship between North Korea and South Korea, and between the Korean peninsula and the world, is uncertain. What would be the implications if the current North Korean government were to fall? This timely book provides a thorough analysis of the complexities of regime change that goes far beyond the usual media discussion of this topic. The book traces the historical roots of the existence of the two Koreas and their ideological divide. It goes on to review the consequences of South Korea$1 (Bs alternating policies of "sternness and sunshine" toward North Korea since World War II, and presents an analysis of their likely relative efficacy in achieving re-unification. The book then examines the effect of international affairs on the prospects for stability and reunification on the Korean peninsula and assesses the relevance of reunification experiences in Germany and Vietnam to Korea$1 (Bs situation. Finally, it suggests how to proceed if the opportunity for reunification arises, tackling the issue of how South Korea can respond to other nations$1 (Binterests in the outcome on the Korean Peninsula and the need for a multinational body to supervise a North Korean transition replacing the present regime. This comprehensive book will be invaluable to any researcher, student, or decision maker interested in the future of the Korean peninsula, East Asian political economy, and international diplomacy.s
Are Koreans Ideological Victims? -- Inter-Korean Economic Cooperation: The Need for Reciprocity. Does Lopsided Cooperation Soothe the North$1 (Bs Bluffing Mentality? -- The Strain Policy Versus the Sunshine Policy: A Road to Korean Unification -- What if a Big Bang Occurs on the Korean Peninsula? -- New World Environment Surrounding Korea -- The Political Economy of Reunification Between the Two Koreas -- Policy Priorities for the Unified Korea -- International Politics and a Search for Unified Korea.s
Keywords: Social sciences; Economic policy; International economics; Regional economics; Political science; Social Sciences; Political Science; Regional/Spatial Science; International Economics; Economic Policy